Potential for Antigen-Specific Tolerizing Immunotherapy in Systematic Lupus Erythematosus - Robinson, Sean; Thomas, Ranjeny (Frontiers in Immunology, 2021)
Systemic lupus erythematosus (SLE) is a chronic complex systemic autoimmune disease characterized by multiple autoantibodies and clinical manifestations, with the potential to affect nearly every organ. SLE treatments, including corticosteroids and immunosuppressive drugs, have greatly increased survival rates, but there is no curative therapy and SLE management is limited by drug complications and toxicities. There is an obvious clinical need for safe, effective SLE treatments. A promising treatment avenue is to restore immunological tolerance to reduce inflammatory clinical manifestations of SLE. Indeed, recent clinical trials of low-dose IL-2 supplementation in SLE patients showed that in vivo expansion of regulatory T cells (Treg cells) is associated with dramatic but transient improvement in SLE disease markers and clinical manifestations. However, the Treg cells that expanded were short-lived and unstable. Alternatively, antigen-specific tolerance (ASIT) approaches that establish long-lived immunological tolerance could be deployed in the context of SLE. In this review, we discuss the potential benefits and challenges of nanoparticle ASIT approaches to induce prolonged immunological tolerance in SLE.